Management for Perforated Mooren’s Ulcer - Linda Wira Putri; Havriza Vitresia; Getry Sukmawati (Majalah Oftalmologi Indonesia, 2015)
Background: To report the surgical management for perforated Mooren's ulcer by performing conjunctival resection with situational corneal suture and Amniotic Membrane Transplantation. Case Illustration: There were six patients diagnosed with Mooren's ulcer between 2011-2013. Three of them were perforated Mooren's ulcer with iris prolaps, and the size of perforation was 2-4 mm. The sex distribution of the patient were 3 male and 3 female patients. The age of presentation of were varied from 11-48 yo. Three patients underwent surgery, one patient refused. The other 2 patients only got medical therapy. For perforated cases with iris prolaps, we performed conjunctival resection with situational corneal suture, overlying the perforation. The suture were made like a net or bridge, depend on cases, and then amniotic membrane were put over the suture. The corneal suture should not be tight because it can disrupt the corneal contour. Amniotic membrane were put on the net layer by layer, and then fixed by interrupted suture to the episclera and cornea, at least in 8 position. The eyes were patching about 4 days and give topical and systemic antibiotic, and corticosteroid systemic. All of patient have complete epithelization after surgery between day 7-10 and have visual acuity improvement. Some of the patient still followed up until now. Conclusion: Conjunctival Resection with situational corneal suture and Amniotic Membrane Transplantation appeared to be an effective procedure for perforated Mooren's ulcer and iris prolaps, even more than 2 mm size of perforation.